2010
DOI: 10.1111/j.1365-2850.2010.01645.x
|View full text |Cite
|
Sign up to set email alerts
|

‘They all said you could come and speak to us’: patients' expectations and experiences of help on an acute psychiatric inpatient ward

Abstract: Acute psychiatric inpatient care forms an integral part of mental health services. Few studies have focussed on the patient experience of acute care. Research into patient experience is increasingly important to policy and service development processes. Knowledge of patient experiences facilitates the development of nursing practice. The aim of the study was to gain insight into the experience of being a patient on an acute inpatient psychiatric ward. Thirteen participants were recruited from the acute ward. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 34 publications
(60 reference statements)
7
83
0
Order By: Relevance
“…These would need to include strategic decisions in the management, philosophy, and priorities of a ward for staff and inpatients to perceive therapeutic interventions as central to an inpatient admission. Such changes could herald a shift in the focus of treatment during a mental health admission from Bcontainment^and Bmanagement^to providing Bprotected time^where it is perceived as a Btherapeutic window of opportunity^and Bteachable moment^ (Stenhouse 2011;Thomson and Hamilton 2012;Butler et al 2014).…”
Section: Limitations and Relevance For Clinical Practicementioning
confidence: 99%
“…These would need to include strategic decisions in the management, philosophy, and priorities of a ward for staff and inpatients to perceive therapeutic interventions as central to an inpatient admission. Such changes could herald a shift in the focus of treatment during a mental health admission from Bcontainment^and Bmanagement^to providing Bprotected time^where it is perceived as a Btherapeutic window of opportunity^and Bteachable moment^ (Stenhouse 2011;Thomson and Hamilton 2012;Butler et al 2014).…”
Section: Limitations and Relevance For Clinical Practicementioning
confidence: 99%
“…Similarly, these findings are supported by Stenhouse (2010Stenhouse ( , 2011, who interviewed service users in inpatient settings, and her aptly titled paper 'They all said you could come and speak to us' detailed service users' expectations, which she reported were not met as participants perceived nurses were too busy with non-nursing tasks. A study by Nolan et al (2016) Delaney and Johnson (2014) identified that whilst the therapeutic relationship with users was viewed as a foundational role, this was actually difficult to achieve:…”
Section: What Mental Health Nurses Domentioning
confidence: 76%
“…Since the advent of recovery oriented approaches, which focuses workers' attention on service users' priorities, the value of service user involvement has been increasingly recognised as good practice (Beresford, 2008;Borg, Karlssen & Kim, 2009). However, whilst this may be heralded as a practice imperative, it is suggested that nurses may struggle to carry out such work (Patton, 2013;Stenhouse, 2011).…”
Section: Why Study Talk About Mental Health Nursing and Service User mentioning
confidence: 99%
See 2 more Smart Citations